Deformation and film formation mechanisms during high velocity impact of silicon carbide nanoparticles. (June 2022) - Davies, Derek W.; Moyers, Aidan H.; Gammage, Michael D.; Keto, John W.; Becker, Michael F.; Kovar, Desiderio
Abstract: Molecular dynamics simulations were conducted to study the factors that affect deformation behavior that occurs during high-speed impact of SiC nanoparticles onto flat substrates. For these simulations, a 6 nm particle was impacted onto a (110)-oriented SiC substrate and the particle impact velocity (3000–4000 m/s), particle orientation, and impact angle (0°–75°) were systematically varied. A broad range of impact behaviors were observed and categorized from elastic with no particle sticking to plastic with significant particle deformation and sticking. High impact velocities and near normal impact angles were found to enhance particle sticking. Particle orientation also had an effect. For some impact conditions, disordering of the lattice within the particle was observed and quantified. Particle impacts that resulted in the greatest degree of amorphization also exhibited significant deformation. This suggests that amorphization followed by viscous flow in the disordered region of the particle is the primary deformation mechanism responsible for particle sticking. Graphical abstract: Image 1 Highlights: Amorphization observed in simulations of high-velocity impacts of SiC nanoparticles. Observed plastic deformation via amorphization and viscous flow. Extent of amorphization is an effective predictor of deformation. Amorphization increases with impact velocity and decreases with impact angle. Particle adhesion is generally correlated with amorphization and plastic deformation.